POLITIK IDENTITAS DALAM PERSPEKTIF POSKOLONIAL STUDI KASUS HIP HOP DANGDUT GRUP NDX A.K.A - Sidjabat, Yedija Remalya; Yulianto, Vissia Ita; Koapaha, Royke Bobby (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2018)
Hip hop dangdut is music identity of NDX A.K.A group. Hip hop dangdut that became popular in society also bring the pros and cons for some groups. Political identity in this research investigates background in choosing music dangdut and hip hop that integrated in NDX’s songs. Political identity used to see the factor that played a role in  formation of hip hop dangdut, but not fully realized by NDX group. Political identity in  formation of hip hop dangdut then analyzed in textual and contextual to answer the contestation of hip hop dangdut in postcolonial perspective. The concept postcolonial in this research is criticized dominance or the form of leadership culture (hegemony) conducted by capitalists. Hip hop dangdut formed because of the hegemony of media in popularizing hip hop that occurs massively. Contestation on hip hop dangdut identity is analyzed using the concept of mimicry and hybridity to see ‘in-between’ space or third space that can be described the position of hip hop dangdut. Negotiations between hip hop and dangdut is a form of hybridity that takes place in ambivalence, which is mimicking and mocking, and not entirely subordinated to the cultural discrimination that occurs to the strategy of globalization. The performance and NDX music that performed on stage shows the cultural identity negotiations between hip hop and dangdut that formed in the third space.